Molecular Characterization of Betasatellite Associated with Begomovirus on Ageratum conyzoides in Magelang, Central Java - Argawi Kandito; Sedyo Hartono; Sri Sulandari; Susamto Somowiyarjo (Jurnal Perlindungan Tanaman Indonesia, 2019)
Ageratum conyzoides is one of the common weeds in Indonesia. The presence of weed can decrease plant yield by resource competition and its role as alternative hosts for pests and diseases, especially begomoviruses transmitted by whitefly. The aim of this research is to detect and characterize the begomovirus-beta satellite in A. conyzoides. A. conyzoides showed severe yellowing symptoms were collected from Magelang, Central Java, Indonesia. Total DNA was extracted and analyzed using PCR method for begomovirus and beta satellite. Begomovirus detection was performed with universal primer Krusty-Homer, resulted a 500 bp DNA fragment. Betasatelit detection performed with specific primer β01/β02, resulted a 1300 bp DNA fragment, indicated presence of a beta satellite associated with the begomovirus. The sequence of begomovirus showed 95% similarity with Tomato Leaf Curl Java Virus (ToLCJaV). The sequence of beta satellites showed 85% similarity with Tomato Leaf Curl Betasatellite (ToLCB). Characterization of beta satellite showed three main characters of beta satellite, TAATATTAC stem-loop structure, Adenine-rich region, and 118 amino acids of putative ORF BC1.